2020
DOI: 10.3390/ijerph17114159
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Addiction and Its Relationship with Health Outcomes in Indoor Cycling Practitioners in Fitness Centers

Abstract: We studied the prevalence and possible association between exercise addiction and health in indoor cycling practitioners. In 1014 (492 women) adult indoor cyclists and 926 (597 women) controls with low levels of physical activity according to the short form of the International Physical Activity Questionnaire, we examined the risk of exercise addiction according to the Exercise Addiction Inventory and several health outcomes through a web-based experiment. The prevalence of a high risk of exercise addiction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Our results are in line with some earlier studies that have demonstrated emotional disturbances in association with exercise addiction, such as a higher level of neuroticism (Birche et al, 2017), more frequent negative mood states and emotions (Costa et al, 2013; Emini & Bond, 2014; Lukács et al, 2019; Sicilia et al, 2020), and increased anxiety and depressive tendencies (Back et al, 2021; Bueno-Antequera et al, 2020; Lukács et al, 2019; Magee et al, 2016). However, the psychological mechanisms between negative emotional states and exercise addiction were still unclear in earlier research.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with some earlier studies that have demonstrated emotional disturbances in association with exercise addiction, such as a higher level of neuroticism (Birche et al, 2017), more frequent negative mood states and emotions (Costa et al, 2013; Emini & Bond, 2014; Lukács et al, 2019; Sicilia et al, 2020), and increased anxiety and depressive tendencies (Back et al, 2021; Bueno-Antequera et al, 2020; Lukács et al, 2019; Magee et al, 2016). However, the psychological mechanisms between negative emotional states and exercise addiction were still unclear in earlier research.…”
Section: Discussionsupporting
confidence: 93%
“…The present study clearly indicated that the dangers of overtraining can cause bodily pain (Marques et al, 2018;Landolfi, 2012;Çetin et al, 2020) highlighting an unhealthy component of exercise. It is suggested that as fitness trends continue to grow, so will prevalence rates of exercise addiction among individuals and should therefore be a potential cause for concern (Marques et al, 2018) and that there is a clear need for multidisciplinary teams (Bueno-Antequera et al, 2020) in order to correctly identify and diagnose exercise addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, given the study that utilised self-report, this may be due to women being more open in discussing their feelings (Juwono & Szabo, 2020). The volume of training for those at risk of exercise addiction has also been found to be significant among 'indoor cycling' (where advanced spinning bikes, or smart bikes, such as Wattbike, often used in combination with training apps such as Zwift), where female cyclists have demonstrated that individuals do not only have to cycle outdoors to be at risk, and those who trained more had increased levels of anxiety (Bueno-Antequera et al, 2020). Another gender difference is that women have been found to have higher levels of obsessive passion at both low and high exercise intensities, although many different sports were included in this sample (Kovacsik et al, 2018) and female cyclists had poorer sleep quality across all volumes of training compared to males (Oviedo-Caro et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hopefully, a large number of papers were published. These high-quality papers covered a wide range of topics in Sports and Health such as different ball games [ 1 , 2 , 3 , 4 , 5 , 6 ], training analyses [ 7 , 8 ], and health aspects such as vitamin D in adolescent athletes [ 9 ], treating obesity and the metabolic syndrome [ 10 , 11 ], infectious diseases such as HIV [ 12 ], exercise addiction [ 13 ], the level of mood and depression [ 14 ], tobacco use in elite athletes [ 15 ], and the aspect of the Covid-19 pandemic [ 16 , 17 ]. We hope that these papers will contribute to the advancement of Sports and Health sciences by offering practical applications for professionals in the field.…”
mentioning
confidence: 99%